Frankenstein new world ebook - Golden, Christopher (Frankenstein., 2023)
Safely tucked away inside the hollow earth where humanity survived after Ragna Rok, precocious young Lilja receives visions of a new darkness taking root on the surface.Defying her elders, Lilja awakens the timeless oracle—once known as Frankenstein—to investigate the warnings and, perhaps, even explore the new world above.Frankenstein: New World, from Mike Mignola, Thomas Sniegoski, Christopher Golden, artist Peter Bergting, and colorist Michelle Madsen, explores a new chapter in the world of Hellboy!Collects Frankenstein: New World #1–#4.